(untitled) (Andamios, Revista de Investigación Social, 2004)
This paper examines some of the most important contributions for the studies on communication and culture, of the academic debate on the reception and production of meaning between James Curran and David Morley. Its purpose is to suggest the relevance of taking some theoretical steps to approach fragments of the city from the point of view of individual experience. In this sense, the author plead for the continuous collaboration and interchange between social sciences, in terms of categories, common theories, concepts, etc. and for an hermeneutic-interpretative position, in order to lighten the fragment of life which is to be studied.